The Handbook of global energy policy - Goldthau, Andreas (Chichester, West Sussex, UK Wiley-Blackwell, 2013)
This is the first handbook to provide a global policy perspective on energy, bringing together a diverse range of international energy issues in one volume. Maps the emerging field of global energy policy both for scholars and practitioners; the focus is on global issues, but it also explores the regional impact of international energy policies. Accounts for the multi-faceted nature of global energy policy challenges and broadens discussions of these beyond the prevalent debates about oil supply. Analyzes global energy policy challenges across the dimensions of markets, development, sustainability, and security, and identifies key global policy challenges for the future. Comprises newly-commissioned research by an international team of scholars and energy policy practitioners
Part I. Global Energy: Mapping the Policy Field -- 1. The Role of Markets and Investment in Global Energy / Albert Bressand -- 2. The Entanglement of Energy, Grand Strategy, and International Security / Meghan L. O'Sullivan -- 3. Sustainability, Climate Change, and Transition in Global Energy / Michael Bradshaw -- 4. The Development Nexus of Global Energy / Gilles Carbonnier and Fritz Brugger -- Part II. Global Energy and Markets -- 5. The Oil Market: Context, Selected Features, and Implications / Christopher Allsopp and Bassam Fattouh -- 6. Natural Gas Going Global? Potential and Pitfalls / Matthew Hilbert and Andreas Goldthau -- 7. The Breakout of Energy Innovation: Accelerating to a New Low Carbon Energy System / Michael LaBelle and Mel Horwitch -- 8. Recent Trends in Upstream Petroleum Agreements: Policy, Contractual, Fiscal, and Legal Issues / Honore Le Leuch -- 9. National Oil Companies: Ensuring Benefits and Avoiding Systemic Risks / Charles McPherson -- Part III. Global Energy and Security -- 10. Global Resource Scramble and New Energy Frontiers / Oystein Noreng -- 11. Cooperation and Conflict in Oil and Gas Markets / Dag Harald Claes -- 12. The "Gs" and the Future of Energy Governance in a Multipolar World / Charles Ebinger and Govinda Avasarala -- 13. Nuclear Energy and Non-Proliferation / Yury Yudin -- Part IV. Global Energy and Development -- 14. Energy Access and Development / Subhes C. Bhattacharyya -- 15. Resource Governance / Andrew Bauer and Juan Carlos Quiroz -- 16. The "Food Versus Fuel" Nexus / Robert Bailey -- 17. Energy Efficiency: Technology, Behavior, and Development / Joyashree Roy, Shyamasree Dasgupta, and Debalina Chakravarty -- Part V. Global Energy and Sustainability -- 18. Regulation, Economic Instruments, and Sustainable Energy / Neil Gunningham -- 19. The Role of Regulation in Integrating Renewable Energy: The EU Electricity Sector / Jaap Jansen and Adriaan van der Welle -- 20. Global Climate Governance and Energy Choices / Fariborz Zelli, Philipp Pattberg, Hannes Stephan, and Harro van Asselt -- 21. The Growing Importance of Carbon Pricing in Energy Markets / Christian Egenhofer -- 22. The Influence of Energy Policy on Strategic Choices for Renewable Energy Investment / Rolf Wüstenhagen and Emanuela Menichetti -- Part VI. Regional Perspectives on Global Energy -- 23. Global Energy Policy: A View from China / Alvin Lin, Fuqiang Yang, and Jason Portner -- 24. Dismounting the Subsidy Tiger: A Case Study of India's Fuel Pricing Policies / Sudha Mahalingam -- 25. The EU's Global Climate and Energy Policies: Gathering or Losing Momentum? / Richard Youngs -- 26. Energy Governance in the United States / Benjamin K. Sovacool and Roman Sidortsov -- 27. Global Energy Policy: A View From Brazil / Suani T. Coelho and José Goldemberg -- 28. Global Oil Market Developments and Their Consequences for Russia / Andrey A. Konoplyanik -- 29. Nigeria: Policy Incoherence and the Challenge of Energy Security / Ike Okonta -- Conclusion : Global Energy Policy: Findings and New Research Agendas / Andreas Goldthau.
Includes bibliographical references and index.
Keywords: Energy policy